Clinical psychologists' implementation of the Mental Capacity Act. Issue 2 (6th May 2014) - Walji, Irram; Fletcher, Ian; Weatherhead, Stephen
Abstract : Purpose: – The purpose of this paper is to present an exploration of the experiences of clinical psychologists involved in implementing the Mental Capacity Act (MCA). Design/methodology/approach: – Seven clinical psychologists were interviewed and transcripts were analysed using thematic analysis. Findings: – Six themes were identified: competence and confidence; understanding and uncertainty; colleagues, collaboration, conflicts, and challenges; working within the law: processes and penalties; the psychological way: specialist skills and difficult decision-making; and power, principles, and protecting the person. The themes highlighted how the specialist skills and professional values of clinical psychologists enhanced their ability to maintain person-centred approaches and uphold the empowering principles underlying the MCA. Data analysis indicated a shared narrative among clinical psychologists involved in implementing the MCA, despite differences in client groups and contexts. Practical implications: – This research highlighted the importance of finding solutions to current problems with the implementation of the MCA, such as training gaps and misunderstanding of the Act in relation to some of its complexities (e.g. deprivation of liberty safeguards and best interests decisions). These areas have the potential to significantly impact on a person's wellbeing. There is an ongoing need for training, multidisciplinary working, and strong effective supervision with ongoing reflexivity, if the Act is to be implemented in the holistic person-centred manner that are the foundations on which it was developed. Originality/value: – This research identifies the important role clinical psychologists have to play in this process. Their specialist skills can encourage a person-centred approach to the implementation of the MCA.